2015
DOI: 10.1111/pan.12608
|View full text |Cite
|
Sign up to set email alerts
|

Selection of subspecialty fellows in anesthesia for pediatric anesthesia: a national survey of program directors in the United States

Abstract: A minority of pediatric fellowship program directors rated prior research experience as an important factor in the selection of prospective fellows. The lack of emphasis on research qualities for fellows is potentially concerning for the future of our specialty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
(20 reference statements)
1
9
0
Order By: Relevance
“…Previous studies identified selection criteria for subspecialty fellowship programs in fields such as anesthesia, otolaryngology, orthopaedics and obstetrics and gynecology. However, very few studies investigate selection criteria of plastic surgery related fellowships 1 2 3 4 5 6 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies identified selection criteria for subspecialty fellowship programs in fields such as anesthesia, otolaryngology, orthopaedics and obstetrics and gynecology. However, very few studies investigate selection criteria of plastic surgery related fellowships 1 2 3 4 5 6 7 .…”
Section: Introductionmentioning
confidence: 99%
“…We also excluded surveys that sample institutions (eg, surveys of fellowship program directors about characteristics of their fellowship program), as response rates to these surveys tend to be very high, possibly owing to respondents' perceived responsibility to complete the survey on behalf of their institution. 19,20 Furthermore, we evaluated quality and impact metrics among published studies, but did not analyze which survey characteristics influenced the likelihood of publication and did not include surveys reported only in the "grey literature" (eg, non-peer-reviewed reports) or surveys conducted internally within professional societies. An additional limitation of examining impact metrics is that only a small number of articles receive scholarly and public attention more than the typical article, such as the Baird et al paper.…”
Section: Discussionmentioning
confidence: 99%
“…E.g., only 39% of pediatric anesthesiology fellowship program directors rated research experience as extremely or very important when evaluating candidates. 23…”
Section: Discussionmentioning
confidence: 99%